2007
DOI: 10.1159/000100411
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and phylogeny of West African gerbils of the genus <i>Gerbilliscus</i> (Muridae: Gerbillinae) inferred from comparative G- and C-banding chromosomal analyses

Abstract: Comparative analysis of the G- and C-banding patterns in six morphologically similar species of the genus Gerbilliscus(G. gambianus, G. guineae, G. kempi, Gerbilliscus sp., G. robustus and G. leucogaster) and one belonging to the genus Gerbillurus (G. tytonis) from 27 West, East and South African localities was carried out. Our study revealed that 17 rearrangements comprising seven fissions, five translocations and five inversions occurred in the evolution of this group, with 1–13 rearrangements differentiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
4
19
0
Order By: Relevance
“…From their diploid number of 50 and chromosome morphology (NFa564 plus large metacentric X and Y chromosomes; Figure 11) they can be unambiguously attributed to G. guineae as recently defined by chromosomal, molecular and morphological studies (Colangelo et al 2001;Granjon 2005;Volobouev et al 2007). All the specimens that can be attributed to this species and have been found in Boké (fallow grassland), Koumbanyi (gallery forest line along Tombani River), and Kandiafara (open woodland, close bush).…”
Section: Subfamily Gerbillinae Gray N1825supporting
confidence: 51%
“…From their diploid number of 50 and chromosome morphology (NFa564 plus large metacentric X and Y chromosomes; Figure 11) they can be unambiguously attributed to G. guineae as recently defined by chromosomal, molecular and morphological studies (Colangelo et al 2001;Granjon 2005;Volobouev et al 2007). All the specimens that can be attributed to this species and have been found in Boké (fallow grassland), Koumbanyi (gallery forest line along Tombani River), and Kandiafara (open woodland, close bush).…”
Section: Subfamily Gerbillinae Gray N1825supporting
confidence: 51%
“…Gerbilliscus has been in recent years the subject of new molecular (Chevret and Dobigny 2005;Colangelo et al 2005Colangelo et al , 2007 and karyological investigations (Qumsiyeh 1986(Qumsiyeh , 1987Qumsiyeh and Schlitter 1991;Volobouev (Qumsiyeh 1986;Qumsiyeh et al 1987Volobouev et al 2007) and mitochondrial DNA (Chevret and Dobigny 2005;Colangelo et al 2007) analyses have revealed a hidden diversity within the Eastern Africa representatives of this genus and a closer affinity to the Southern African genus Gerbillurus. Furthermore, molecular data suggests that the taxonomy and systematics of this genus, traditionally based only on external and cranial morphology (for a revision of east African species see Bates 1985Bates , 1988, present several pitfalls due to the limited discriminating values of some morphological characters previously used to classify the species.…”
Section: Introductionmentioning
confidence: 99%
“…The incongruence between morphological and genetic species boundaries which has become evident in recent years and the possible occurrence of cryptic species within the genus Gerbilliscus (Colangelo et al 2007;Volobouev et al 2007) suggest that a critical review of the taxonomy and systematics of the genus is required.…”
Section: Introductionmentioning
confidence: 99%
“…In some mammalian taxa, particularly rodents, comparative chromosome banding studies have been extremely helpful in clarifying the systematic position of species which do not display clear affinities when assessed by morphological or/and molecular genetic characters (Taylor, 2000;Volobouev et al, 2002aVolobouev et al, , b, 2007Dobigny et al, 2003a). In the case of the Bovidae, however, in spite of the large interspecific variation in diploid numbers and chromosome morphology, chromosome banding has convincingly shown that this variation is largely attributable to Robertsonian (Rb) rearrangements (Wurster and Benirschke, 1968;Buckland and Evans, 1978;Gallagher and Womack, 1992) most of which are species-specific (i.e.…”
mentioning
confidence: 99%